Changes in Delivery Timing for High-Risk Pregnancies in the United States. Issue 5 (May 2022) - Little, Sarah E.; Robinson, Julian N.; Zera, Chloe A.
Abstract : (Abstracted from Am J Perinatol 2021;38:1373–1379) Awareness of increased morbidity in neonates born at 34 to 37 weeks' gestation (late preterm) and 37 to 39 weeks' gestation (early term), compared with those born at ≥39 weeks' gestation, has grown over the past decade. As a result, efforts have been put in place in hospitals and at state and national levels to reduce deliveries at <39 weeks of gestation that are not medically indicated.